Environmental impacts of sugar production : the cultivation and processing of sugarcane and sugar beet - Cheesman, Oliver (CABI, 2004)
This book contains 8 chapters on the environmental impact of the cultivation and processing of sugarcane and sugarbeet. The chapters are entitled: (1) background; (2) overview; (3) water consumption; (4) impacts on water quality and aquatic ecosystems; (5) impacts on terrestrial biodiversity; (6) impacts on soils; (7) atmospheric impacts; and (8) use and impacts of byproducts. This book will be of significant interest to policymakers, industry practitioners and researchers in sugar, crop, soil, water and environmental sciences.